LITERATUR REVIEW PENGARUH PEMBERIAN AIR KELAPA HIJAU TERHADAP PENURUNAN DISMENORE PADA REMAJA TAHUN 2020 - Melva; Prastika, Febiola; Sembiring, Arihta; Desfauza, Evi (Colostrum Jurnal Kebidanan, 2021)
Dysmenorrhea is a state of great pain and can interfere with daily activities in women, especially young women. Dysmenorrhea is an asymptomatic phenomenon including abdominal pain, cramps, and back pain. One way to treat pain in dysmenorrhea is to use green coconut water because green coconut water contains Calcium 14.11 Mg / 100 ml, Magnesium 9, 11 Mg / 100 ml, and Vitamin C of 8.59 Mg / 100 ml. This literature review aims to determine the effect of green coconut water giving on reducing dysmenorrhea in adolescents. This research method was a literature review. The type of data used was secondary data. The technique of collecting data through the documentation method was by the inclusion criteria. The results of the literature review showed that there was an effect of green coconut water giving on reducing dysmenorrhea in adolescents. It is suggested that the results of the literature review can be used as a source of information for educational institutions, especially midwifery, to find out the benefits of green coconut water to overcome dysmenorrhea that often occurs in girls.